La missió en la vida. Notes sobre «Camins de França» de Joan Puig i Ferreter - Balaguer, Enric (Caplletra. Revista Internacional de Filologia, 2005)
This article approaches the task of analyzing the autobiographical activity of Joan Puig i Ferrater. Particular attention is paid to «Camins de França», one of the mostoutstanding autobiographies of the twentieth century literature. The literary production of Puig i Ferreter turns around a series of basic characteristics: life like an initiation journey, life like a search of the affirmation of his own personality, and the sense ofsensuality. All in all, the author conceives his office of artist as an adventure in search of his own essence.